Pembrolizumab plus chemotherapy for first-line treatment of metastatic nonsquamous non-small-cell lung cancer: a network meta-analysis. (4th February 2019) - Frederickson, Andrew M; Arndorfer, Stella; Zhang, Ina; Lorenzi, Maria; Insinga, Ralph; Arunachalam, Ashwini; Burke, Thomas A; Simon, George R
Aim: A systematic review and network meta-analysis were conducted to evaluate the efficacy of pembrolizumab + pemetrexed + platinum relative to other regimens in metastatic nonsquamous non-small-cell lung cancer (NSq-NSCLC).Patients & methods: Eligible studies evaluated first-line regimens in NSq-NSCLC patients without known targetable mutations. Relative treatment effects were synthesized with random effects proportional hazards Bayesian network meta-analyses.Results: The hazard ratio (HR) for overall survival (OS) for pembrolizumab + pemetrexed + platinum was statistically significant over all platinum-doublet (HR range: 0.42–0.61), platinum-doublet + bevacizumab (HR range: 0.44–0.53) and platinum-doublet + atezolizumab regimens (HR range: 0.56–0.62). Additionally, pembrolizumab + pemetrexed + platinum numerically improved OS over atezolizumab + paclitaxel + carboplatin + bevacizumab (HR: 0.65; 95% credible interval: 0.43, 1.01). Pembrolizumab + pemetrexed + platinum had 95.6% probability of being the best treatment regimen for OS.Conclusion: Pembrolizumab + pemetrexed + platinum is likely the most efficacious first-line regimen for metastatic NSq-NSCLC.